Economics and Law of Trade in Services - Mattoo, Aaditya (World Bank, Washington, DC, 2017)
Services are the fastest growing sector of the global economy, and trade and foreign direct investment in services have grown faster than in goods over the past decade. Technological progress has greatly enhanced the scope for trade in conventional services, such as education and finance, and also created a host of new tradable services,such as software development and internet access. Moreover, liberalization in many countries is leading for the first time to the private and foreign provision of services such as telecommunications, transport, and finance. The performance of the services sectors can make the difference between rapid and sluggish growth.But the benefits from liberalization are not automatic. Multilateral engagement can be an important catalyst for liberalization. Even though governments can initiate reforms of services individually, multilateral engagement can help in two ways. First, international negotiations, for example under the General Agreement on Trade in Services (GATS), could help accelerate domestic reform and improve access to foreign markets for developing countries. However, for these negotiations to be fruitful, all countries must recognize mutual interests in reciprocal liberalization. Developing countries must see advantages of multilateral agreement to increase competition, to enhance credibility of potential domestic reform and to strengthen domestic regulation.In parallel, global cooperation is needed to provide support for developing countries at four levels: in devising sound policy, strengthening the domestic regulatory environment,enhancing their participation in the development of international standards and in ensuring access to essential services in the poorest areas.